Enhancing date seed phenolic bioaccessibility in soft cheese through a dehydrated liposome delivery system and its effect on testosterone-induced benign prostatic hyperplasia in rats - Mohammed, Dina Mostafa; El-Messery, Tamer M.; Baranenko, Denis A.; Hashim, Mahmood A.; Boulkrane, Mohamed Said; El-Said, Marwa M. (Frontiers in Nutrition, 2023)
The consumption of dairy products, including soft cheese, has been associated with numerous health benefits due to their high nutritional value. However, the phenolic compounds bioaccessibility present in soft cheese is limited due to their poor solubility and stability during digestion. So, this study aimed to develop an innovative soft cheese enriched with date seed phenolic compounds (DSP) extracted ultrasonically and incorporated into homogeneous liposomes and studyits attenuation effect on testosterone-induced benign prostatic hyperplasia (BPH) in rats.Date seed phenolic compounds were extracted using 98% and 50% ethanol along with water as solvents, employing ultrasonication at 10, 20, and 30-minute intervals. The primary and secondary DSP-liposomes were prepared and dehydrated. The particle size, zeta potential, encapsulation efficiency, and morphology were measured. Incorporating dehydrated liposomes (1-3% w/w) into soft cheese and their impact on BPH using male Sprague-Dawley rats was assessed. After inducing BPH, rats were fed a cheese diet with dehydrated DSPliposomes. Over eight weeks, parameters including nutrition parameters, prostate enlargement analysis, biochemical parameters, hormones level, oxidative stress, and cytokines were analyzed.The results showed that ultrasound-assisted extraction effectively reduced the extraction time and 30 mins extraction EtOH 50 % was enough to extract high yield of phenolic compounds (558 mg GA/g), flavonoids (55 mg qu/g) with high antioxidant activity (74%).The biological results indicate that prostate weight and prostate index% were diminished in the treatment groups (1 and 2) compared to the BPH control group. The high antioxidant content present in the DSPliposomes acted as the catalyst for suppressing the responses of the inflammatory cytokines, inhibiting the anti-inflammatory IL-10 production and suppressing the elevated levels of lipid peroxidation products compared to the BPH group. In conclusion, the treatment group (2) supplemented with dehydrated secondary DSP-liposomes exhibited the most significant variance (P < 0.05) as opposed to the BPH group. Liposomal encapsulation was proved to be a feasible approach for administering DSP in soft cheese, thereby establishing new functional food category possessing prophylactic properties against the advancement of BPH in rats.